1994
DOI: 10.1042/bj3020229
|View full text |Cite
|
Sign up to set email alerts
|

Purification of enzymes of the kallikrein gene family (rK8 and rK9) from the rat prostate

Abstract: The rat kallikrein family consists of multiple closely related proteins. A method for demonstration and identification of kallikrein-like proteins has been developed based on their differences in isoelectric point and their immunological similarity. The method, which involved separation in flat-bed isoelectro-focusing gels (pH range 3-9) and detection by immunoblotting using polyclonal antiserum against one of the family members, has been used in the present study to detect kallikrein-like proteins in the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…These proteinases were characterized as serine proteinases since their activities were inhibited by serine proteinase inhibitors. The 30-kDa serine proteinase could represent the major rat prostatic kallikrein, rK9 or rK8, based on its similarity in molecular size (25±30 kDa) and inhibition by aprotinin [59,60]. However, the identity of the 100-kDa serine proteinase is still uncertain.…”
Section: Figs 21^23mentioning
confidence: 99%
“…These proteinases were characterized as serine proteinases since their activities were inhibited by serine proteinase inhibitors. The 30-kDa serine proteinase could represent the major rat prostatic kallikrein, rK9 or rK8, based on its similarity in molecular size (25±30 kDa) and inhibition by aprotinin [59,60]. However, the identity of the 100-kDa serine proteinase is still uncertain.…”
Section: Figs 21^23mentioning
confidence: 99%
“…Identification of kallikrein-like proteins can be difficult because of their similarities in substrate and inhibitor specificity, antigenic epitopes, amino acid sequence, and molecular mass [22]. In the present study, after SDS-PAGE analysis and blotting, the kallikreinlike nature of the prostate protein (p18) was verified by partial amino acid sequencing.…”
Section: Discussionmentioning
confidence: 75%
“…Although the incidence of hypertrophy of the canine prostate increase with age and closely resembles that in humans, BPH have been experimentally induced in rats following prolonged treatment with testosterone. [131415] As androgen exhibited stimulating action on the growth of prostate cell, Testosterone and related hormones are demonstrated to play an important role in disease. [3] Data from large scale clinical study have demonstrated that treatment with 5α-reductase inhibitors not only significantly ameliorates symptoms, but also reduces the long-term risk of progression in patients treated surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Homogenates were centrifuged at 13,000× g for 20 min and supernant collected. [15] Supernant was used as source of proteins and concentration was determined by modified biuret end point assay method.…”
Section: Methodsmentioning
confidence: 99%